PENGARUH INTERPERSONAL SKILL TERHADAP KINERJA DENGAN DIMEDIASI OLEH INTERAKSI SOSIAL SESAMA REKAN KERJA - Sutarman; Agus Seswandi; Adolf Bastian (Ekomania, 2024)
The aim of this research is to determine the influence of Interpersonal Skills on the performance of elementary school teachers in Padang Lawas Regency, North Sumatra Province and the role of social interactions among co-workers in mediating the relationship between these two variables. The method used in this research is descriptive quantitative with a survey approach via questionnaires. The population in this study were teachers in Padang Lawas Regency, North Sumatra Province with a sample size of 71 respondents. Statistical data analysis using the Smart PLS program. The results of this research show that Interpersonal Skills and social interaction between colleagues have a direct and significant influence on the performance of teachers in Padang Lawas Regency, North Sumatra Province. Interpersonal Skills also have a direct positive and significant effect on social interactions between co-workers. Social interaction between co-workers is able to mediate the relationship between Interpersonal Skill and teacher performance in Padang Lawas Regency, North Sumatra Province.